The Effect of Student Motivation on Learning Outcomes in the Tawhid Science Course - Mundofi, Ahmad Asron; Hidayat, Nur; Nurmahni, Nurmahni; Fahrudi, Emi; Urokhim, Auliya (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padngsidimpuan, 2024)
This research aims to analyze the influence that occurs on student motivation on learning outcomes in the Tauhid Science course carried out at the Sunan Kalijaga State Islamic University, Yogyakarta, using a quantitative approach. The method used is the descriptive and inferential correlation method with Analysis of Variance to see the influences, differences, and interactions that occur in the learning outcomes of the Tauhid Science course which are reviewed based on learning motivation. The population in this study included all postgraduate students in the Islamic Religious Education study program with a sample of 62 students consisting of 29 students in class A, 22 B, and 11 students in C. In this research, it was found that student motivation and learning outcomes in monotheism courses did not provide a significant correlation with strengths that were classified as weak. The differences in student learning outcomes occurred in class A and class C, and between the other two classes, there was no significant difference. Apart from that, student learning outcomes based on male and female gender did not provide significant differences or interactions. So, for further research, it is hoped that research can be carried out that correlates student learning outcomes with the learning model used based on reviewing initial abilities regarding the Science of Tauhid to see the influence and improvement that occurs.